CCNoC: Specializing On-Chip Interconnects for Energy Efficiency in Cache-Coherent Servers - Volos, Stavros; Seiculescu, Ciprian; Grot, Boris; Pour, Naser Khosro; Falsafi, Babak, Giovanni De Micheli (6th International Symposium on Networks-on-Chip, 2012)
Many core chips are emerging as the architecture of choice to provide power efficiency and improve performance, while riding Moore's Law. In these architectures, on-chip inter-connects play a pivotal role in ensuring power and performance scalability. As supply voltages begin to level off in future technologies, chip designs in general and interconnects in particular will require specialization to meet power and performance objectives. In this work, we make the observation that cache-coherent many core server chips exhibit a duality in on-chip network traffic. Request traffic largely consists of simple control messages, while response traffic often carries cache-block-sized payloads. We present Cache-Coherence Network-on-Chip (CCNoC), a design that specializes the NoC to fit the demands of server workloads via a pair of asymmetric networks tuned to the type of traffic traversing them. The networks differ in their data path width, router micro architecture, flow control strategy, and delay. The resulting heterogeneous CCNoC architecture enables significant gains in power efficiency over conventional NoC designs at similar performance levels. Our evaluation reveals that a 4×4 mesh-based chip multiprocessor with the proposed CCNoC organization running commercial server workloads is 15-28% more energy efficient than various state-of-the-art single- and dual-network organizations.